Legal Framework for Telemedicine in Georgia: Doctrinal and Comparative Legal Analysis of International Standards and National Practices - Nato Tchitanava (European Scientific Journal, ESJ, 2026)
Based on national and international practice, this article discusses telemedicine as a set of legal, technological, and ethical decisions that are an inevitable result of the modern healthcare system. This article aims to assess the adequacy of Georgia’s regulatory framework for telemedicine through a comparative analysis of international standards and national legislation, and to identify existing legal gaps.From the perspective of international law, the right to health is recognized as a fundamental human right, obligating states to ensure the accessibility, quality, and continuity of medical services for all citizens. Accordingly, the study focuses on the possibilities of telemedicine, which is an effective mechanism for providing continuous and high-quality medical services, especially in geographically remote, rural, and politically/strategically challenging regions.The research is based on doctrinal legal analysis, comparative examination of international and Georgian normative acts, and analysis of relevant case law. International instruments and standards examined include World Health Organization (WHO) recommendations, ISO 13131:2021, the EU General Data Protection Regulation (GDPR), and the U.S. Health Insurance Portability and Accountability Act (HIPAA), and relevant jurisprudence of European and U.S. courts. Georgian healthcare, medical practice, and data protection legislation were analyzed to assess regulatory compatibility and implementation practice. Taking into account the realities of Georgia, the article analyzes national legislation and the existing practice of developing telemedicine. Special attention is paid to the possibilities of implementing telemedicine in politically and strategically difficult regions as one of the effective mechanisms for ensuring continuous and high-quality medical services for the population.Based on the results of the study, which is based on the analysis of international practice and regulatory standards, the article presents recommendations for strengthening the legal framework of telemedicine in Georgia, which takes into account the protection of patient rights, strengthening professional responsibility standards, and improving access to medical services in politically and strategically difficult regions.The study reveals that although Georgian legislation allows telemedicine within the framework of general medical regulation, it lacks: a unified legal definition of telemedicine; specific binding standards for remote informed consent procedures; detailed regulation of cross-border and regional licensing issues; explicit clinical quality assurance mechanisms tailored to remote healthcare services; and specialized liability rules adapted to digital medical practice. International standards demonstrate a trend toward harmonization based on patient rights protection, data security, professional accountability, and technological interoperability, while Georgia’s framework remains fragmented and indirectly regulated.To strengthen the legal framework for telemedicine in Georgia, the study recommends: adopting a comprehensive legal definition and regulatory act dedicated to telemedicine; establishing mandatory digital informed consent standards; introducing telemedicine-specific certification and liability provisions; strengthening state supervision and quality control mechanisms; and improving legal guarantees for safe telemedicine practice in politically and geographically complex regions. The development of a coherent telemedicine regulatory model would contribute to the effective realization of the right to health, enhance access to quality medical services, and align Georgian practice with evolving international standards.